A Study Of Language Learning Strategies Of Male And Female Elementary School Pupils In Learning English In SDN Pabelan 02 Kartasura - Wahyuningtyas, Rahmawati (2006)
The teachings of English in elementary school as a local content subject is due to commence in the 2004/2005 academic years. This present research is done to anticipate the implementation of the teaching of English in the elementary school. The present study is an attempt to find out the description of the profile of language learning strategies of pupils in the elementary school and the differences between males and females in language learning strategies. The study involved the pupils of SDN Pabelan 02 Kartasura grades four, five, and six as the research subjects. On the basis of Oxford's theory, one instrument (Observation Guide) was constructed. The instrument was first tried out to 104 pupils. The data were analyzed using descriptive analysis by answering the questions and percentages about learning strategies. The result of the analysis shows that the pupils of SDN Pabelan 02 Kartasura have relatively high use of three strategies: Cognitive, Compensation, and Affective strategies. Females and males showed their best tendency on cognitive strategy. The results also revealed that there is no significant difference between males and females in their learning strategies.